Thermoelectric Properties of Novel Semimetals: A Case Study of YbMnSb2. Issue 7 (9th December 2020) - Pan, Yu; Fan, Feng‐Ren; Hong, Xiaochen; He, Bin; Le, Congcong; Schnelle, Walter; He, Yangkun; Imasato, Kazuki; Borrmann, Horst; Hess, Christian; Büchner, Bernd; Sun, Yan; et al.
Abstract: The emerging class of topological materials provides a platform to engineer exotic electronic structures for a variety of applications. As complex band structures and Fermi surfaces can directly benefit thermoelectric performance it is important to identify the role of featured topological bands in thermoelectrics particularly when there are coexisting classic regular bands. In this work, the contribution of Dirac bands to thermoelectric performance and their ability to concurrently achieve large thermopower and low resistivity in novel semimetals is investigated. By examining the YbMnSb2 nodal line semimetal as an example, the Dirac bands appear to provide a low resistivity along the direction in which they are highly dispersive. Moreover, because of the regular‐band‐provided density of states, a large Seebeck coefficient over 160 µV K −1 at 300 K is achieved in both directions, which is very high for a semimetal with high carrier concentration. The combined highly dispersive Dirac and regular bands lead to ten times increase in power factor, reaching a value of 2.1 mW m −1 K −2 at 300 K. The present work highlights the potential of such novel semimetals for unusual electronic transport properties and guides strategies towards high thermoelectric performance. Abstract : Single crystals of the YbMnSb2 nodal line semimetal demonstrate the synergetic contribution of Dirac bands and regular band to the thermoelectric performance. A high power factor over 2.1 mW m −1 K −2 is achieved due to both high mobility and large thermopower.